Surface irrigation potential assessment of Chacha River Watershed, Jemma subbasin of upper Blue Nile, Ethiopia - Getahun, Yitea Seneshaw; Gebremedhn, Abrha Ybeyn; Lemma, Estifanos; Tesfay, Fikrey; Tadesse, Solomon Ayele (Frontiers in Environmental Science, 2023)
Evaluation of water availability and land suitability for surface irrigation practice is crucial for a country like Ethiopia whose livelihood is highly dependent on seasonal rainfed agriculture, which is susceptible to climate change and has a large population suffering from food insecurity. In this study, several factors, such as slope, land use land cover, rainfall, proximities to (market centers, roads, and rivers), and soil factors (i.e., pH, organic carbon, cation exchange capacity, electrical conductivity, available water storage capacity, drainage, depth, texture, and soil type) were considered. The data were entered and analyzed using GIS tool and multicriteria analysis of Analytical Hierarchy Process (AHP) to determine the suitable area for surface irrigation in the Chacha Watershed. Subsequently, a CROPWAT tool was used to check the water requirement of the dominant crops grown in the study watershed, while a flow duration curve of 90-percentile exceedance frequency of monthly average streamflow was carried out to identify the minimum available water flow in the Chacha River. The findings of the suitability assessment revealed that 13,336.53 ha (11.78%), 58,357.40 ha (51.57%), 37,588.10 ha (33.21%), and 3,887.96 ha (3.44 %) of lands found in the study watershed are highly suitable, moderately suitable, marginally suitable, and unsuitable for surface irrigation, respectively. The crop water requirement was estimated to be 7 l/s per hectare, and the minimum available water flow was estimated at 87 l/s that can potentially irrigate about 9,280 ha of land with an average of 10-days of watering interval using surface irrigation. However, the current irrigated land in the study watershed was found to be 2159.83 ha implying that the existing surface irrigation practice is quite limited in the watershed though water availability is not a limiting factor. Hence, the government and other concerned bodies should exhaustively work to develop irrigation projects and practices to maximally utilize the available water and the suitable land resources to enhance agricultural productivity. In return, it ameliorates the livelihoods of the communities and thereby help ensure food security in the study watershed.